Access to Bank Credit in Sub-Saharan Africa : Key Issues and Reform Strategies - Sacerdoti, Emilio (IMF Working Papers; Working Paper ;, 2005)
This study discusses issues of access to bank credit in Sub-Saharan Africa, and examines measures that could help facilitate access by the private sector to bank credit. It reviews in particular obstacles to credit small- and medium-scale enterprises and agriculture, and examines progress in the design and implementation of reform measures that are needed to create an institutional environment more supportive of credit activity. It also reviews bank interest rate spreads and profit margins, and their determinants, and compares such spreads with those prevailing in other regions of the world.